Ekologiczna reforma podatkowa jako jeden z elementów przemian finansów publicznych państwa - Jakubczyk, Zbigniew; Janicki, Marek (Ecological reform of the tax system as an element of reforming public finance, 2006)
In the article the concept of ecological reform of tax system as an element of reforming public finance in Poland is discussed. First, the direction of change in economic instruments used for environmental protection is presented within the context of Poland’s EU accession. Second, the basis of ecological reform of the system is discussed. Third, potential threats and benefits connected with the implementation of reforms are described. It is argued that ecological reform of the tax system should be implemented within the context of change in other areas of public finances. A conclusion is that the implementation of reforms should be evolutionary and should be accompanied by protective measures.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Gospodarka a Środowisko (5); 2006; nr 1115, s. 121-127